Characteristics of small business leadership from employees' perspective: A qualitative study. (April 2019) - Putra, Eka Diraksa; Cho, Seonghee
Highlights: This study explored the ideal characteristics for small independent restaurant leaders using a qualitative approach from employees' perspectives. A qualitative approach was employed because of (a) the unique operations of small independent restaurants that affect their owners' management styles and (b) the lack of leadership studies on small hospitality businesses. This paper has attempted to address the gap in knowledge by attempting to understand the ideal characteristics for the leadership of small independent restaurants as portrayed by employees. The findings showed nine themes emerged that revealed specific leadership qualities as reported by the participants: respectful, compassionate, effective communicator, experienced, effective delegator, gives recognition, sociable, emotional controlled, and organized. Abstract: Leadership is a much-studied topic, and yet, the topic still attracts researchers. As an essential factor in every organization, however, leadership contributes significantly to a business failure, especially in small independent restaurant businesses and this could be due to the unique operations of the industry and the lack of leadership studies on small hospitality businesses. This study aims to fill the gap by exploring the ideal characteristics for small independent restaurant leaders to become an effective leader using a qualitative approach from their employees' perspectives. Qualitative data were collected through four focus groups and one dyadic interview. The findings of the qualitative data analysis revealed nine themes: respectful, compassionate, effective communicator, experienced, effective delegator, gives recognition, sociable, emotionally controlled, organized. The paper discussed implications of the findings for small independent restaurant businesses and the hospitality industry in general as well as implications for theory.